Effect of consolidation pressure on the impact behavior of UHMWPE composites. (15th August 2018) - Lässig, Torsten R.; May, Michael; Heisserer, Ulrich; Riedel, Werner; Bagusat, Frank; van der Werff, Harm; Hiermaier, Stefan J.
Abstract: For the first time, the influence of the manufacturing process on the dynamic performance of ultra-high molecular weight polyethylene (UHMWPE, Dyneema ® HB26) composites is investigated. The material is significantly influenced by the hot-pressing parameters temperature and pressure. The ballistic resistance and shock wave behavior was characterized for the UHMWPE composite consolidated with three different pressures. In the case of UHMWPE composites, higher consolidation pressures result in a better ballistic performance. The shock wave behavior converges to high-density polyethylene (HDPE). Based on these observations, an analytical approach is proposed describing the equation of state as a function of consolidation pressure.